Call the Midwife - Health Personnel and Mortality in Norway 1887-1921 - Andreas Kotsadam; Jo Thori Lind; Jørgen Modalsli (Center for Economic Studies and ifo Institute (CESifo), 2017)
The Nordic countries have the lowest maternal and child mortality rates in the world. This has not always been the case. In 1887 the mortality rates in Norway were similar to those of developing countries today. During the next 34 years, Norwegian maternal mortality was halved and infant mortality fell by 40 percent. Investigating the relationship between health personnel and mortality at the local level during this period, we find a large and robust effect of midwives on reduced maternal mortality. No clear effect is found for other types of health personnel or on infant mortality.
Keywords: H41; I18; N33; 330; health policy; public service provision; history; mortality